2018
DOI: 10.1016/j.jweia.2018.05.017
|View full text |Cite
|
Sign up to set email alerts
|

High-order detached eddy simulation of unsteady flow around NREL S826 airfoil

Abstract: In the vast majority of cases, winds are considered to be stationary and as such are treated in the same way for design purposes. However, not all wind is the same, and non-stationary winds such as thunderstorm downbursts and tornadoes need to be considered using a different framework. This paper outlines two possible analytical models for such winds and introduces a possible framework which may be of use to the urban designer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…They investigated the influences of computational mesh resolution and spanwise size on the computational results [17]. Yalçın et al improved the DDES model by two different length scale definitions [18]. It was found that compared with DDES, the results of shear-layer-adapted DDES (SLADDES) were better, in agreement with the experiments.…”
Section: Introductionmentioning
confidence: 83%
“…They investigated the influences of computational mesh resolution and spanwise size on the computational results [17]. Yalçın et al improved the DDES model by two different length scale definitions [18]. It was found that compared with DDES, the results of shear-layer-adapted DDES (SLADDES) were better, in agreement with the experiments.…”
Section: Introductionmentioning
confidence: 83%
“…Xu et al [32] investigated the flow over airfoils at a wide range of attacks. Yalçın et al [33] explored the effects of two different length scale definitions in the simulation of the flow around an airfoil. Wang et al [34] discussed the effects of the time step, spanwise lengths, and grid resolution on the prediction of flow around an airfoil beyond stall.…”
Section: Of 20mentioning
confidence: 99%